2018
DOI: 10.1101/391607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonsteroidal anti-inflammatory drugs alter the microbiota and exacerbate Clostridium difficile colitis while dysregulating the inflammatory response

Abstract: Word count = 143 23Text word count = 5339 24 . CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint . http://dx.doi.org/10.1101/391607 doi: bioRxiv preprint first posted online Aug. 14, 2018; 2 Abstract 25Clostridium difficile infection (CDI) is a major public health threat worldwide. The use of 26 nonsteroidal anti-inflammatory drug… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 82 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…reported that the risk of Clostridium difficile -associated diarrhea was increased among patients exposed to NSAIDs ( Permpalung et al., 2016 ), and indomethacin can increase severity of Clostridium difficile infection in mouse model ( Muñoz-Miralles et al., 2018 ). Further research showed that NSAIDs alter the gut microbiota and exacerbate Clostridium difficile colitis ( Maseda et al., 2019 ). These results revealed that NSAIDs could cause Clostridium difficile infection, which exacerbates intestinal damage by releasing two protein exotoxins (TcdA and TcdB) ( Leffler and Lamont, 2015 ).…”
Section: Alternations Of Gut Microbiota In Nsaid Enteropathymentioning
confidence: 99%
“…reported that the risk of Clostridium difficile -associated diarrhea was increased among patients exposed to NSAIDs ( Permpalung et al., 2016 ), and indomethacin can increase severity of Clostridium difficile infection in mouse model ( Muñoz-Miralles et al., 2018 ). Further research showed that NSAIDs alter the gut microbiota and exacerbate Clostridium difficile colitis ( Maseda et al., 2019 ). These results revealed that NSAIDs could cause Clostridium difficile infection, which exacerbates intestinal damage by releasing two protein exotoxins (TcdA and TcdB) ( Leffler and Lamont, 2015 ).…”
Section: Alternations Of Gut Microbiota In Nsaid Enteropathymentioning
confidence: 99%
“…Treatment of vancomycin reshaped the gut microbiome composition and improved intestinal barrier function by increasing the tight junction proteins (Occludin, ZO-1) (89). Traditional standard treatments for autoimmunity have been immunosuppressive medications that dampen the immune system non-specifically and alter the gut microbiome composition (111,112). Furthermore, microbiome-drug interactions also provide mechanistic insight into the role of gut microbiota in drug efficacy and toxicity (113).…”
Section: Effect Of Antibioticsmentioning
confidence: 99%
“…Moreover, in the work from Saleh et almice have been exposed to gut inflammation; they actually showed that colitis induces a population of Th17 cells that persists beyond the resolution of inflammation, and that this population predisposes the host to severe subsequent CDI. In another work, mice treated with nonsteroidal anti-inflammatory drugs, such as indomethacin, developed a more severe CDI that was correlated with an increase of the Th17 response 123. However, since they do not show a causal relationship, it remains unclear whether Th17 cells alone are necessary and sufficient to exacerbate CDI severity in indomethacintreated mice.It is important to highlight that even less is known about the role of IL-17 in human.…”
mentioning
confidence: 99%